Pengaruh Islam dan Budaya dalam Pembentukan Hukum dI Indonesia - Ja'far Baehaqi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2016)
ABSTRACT There is a relationship between Islam and culture on the one hand and the law on the other. This paper attempts to answer the question about the influence of Islam and the culture in the formation of law in Indonesia. Through a systems approach gained answer that Islam and culture in Indonesia plays an important role in creating social order and piety. As a comprehensive belief system that includes the dimensions of the hereafter and worldly at the same time Islam play the role as a source of inspiration and legitimacy. Meanwhile, as a product of human in responding to natural and life lived culture played a role as a way of life and behavior on the side of religion. As a means to create order and a tool of social engineering, law in Indonesia can not be separated from Islam and culture. Establishment of state law will inevitably have to consider Islam and culture. If not, then the law will be alienated and lose relevance.